DOI: 10.4203/ccp.104.122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ballast Fouling on Rail Tracks

Abstract: Ballast fouling is understood as major cause of track deterioration in many countries over the world. It decreases the drainage and load bearing capacity of the ballast layer. A series of large scale hydraulic conductivity tests were conducted with different proportions of fouling to access the drainage capacity of the track. A numerical analysis was conducted using SEEP/W to quantify the drainage capacity of ballast under different degrees of fouling. Subsequently, track drainage classification in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…They are followed by subgrade intrusion (3%) and sleeper wear (1%) [42]. Ballast fouling has been emphasized to greatly undermine the stability and strength of railway track by many researchers [36,43]. Further, ballast fouling may cause drainage issues in ballasted track since the voids are filled up and water is blocked, leading to higher levels of moisture accumulating in the track substructure [44].…”
Section: Ballast Fouling Mechanismmentioning
confidence: 99%
“…They are followed by subgrade intrusion (3%) and sleeper wear (1%) [42]. Ballast fouling has been emphasized to greatly undermine the stability and strength of railway track by many researchers [36,43]. Further, ballast fouling may cause drainage issues in ballasted track since the voids are filled up and water is blocked, leading to higher levels of moisture accumulating in the track substructure [44].…”
Section: Ballast Fouling Mechanismmentioning
confidence: 99%
“…[43][44][45] In addition, it has been demonstrated that different fouling materials have different effects on hydraulic conductivity; for example, a small increase in VCI of the clay fouled ballast significantly decreased the hydraulic conductivity. 46 Another study indicated that the hydraulic conductivity of fouled ballast converged to that of fouling materials with high VCI (VCI>90% and VCI>50% for clay and coal, respectively). 47 Another study showed that clay contamination reduced the hydraulic conductivity more than coal contamination when the VCI exceeded 50%; however, they acted in the opposite direction at VCI<50%.…”
Section: Mechanism Of Fouling Ballastmentioning
confidence: 97%
“…They are followed by subgrade intrusion (3%) and sleeper wear (1%) [27]. It should be noted that ballast fouling greatly undermines the stability and strength of the railway track as mentioned by many researchers [28,29]. Further, ballast fouling may cause drainage issues in ballasted track since the voids are filled up and water is blocked, leading to higher levels of moisture accumulating in the track substructure [30].…”
Section: Ballast Degradationmentioning
confidence: 99%